Phenotypic Alterations in Erythroid Nucleated Cells of Spleen and Bone Marrow in Acute Hypoxia - Kirill Nazarov; Roman Perik-Zavodskii; Olga Perik-Zavodskaia; Saleh Alrhmoun; Marina Volynets; Julia Shevchenko; Sergey Sennikov (Cells, 2023)
Hypoxia leads to metabolic changes at the cellular, tissue, and organismal levels. The molecular mechanisms for controlling physiological changes during hypoxia have not yet been fully studied. Erythroid cells are essential for adjusting the rate of erythropoiesis and can influence the development and differentiation of immune cells under normal and pathological conditions. We simulated high-altitude hypoxia conditions for mice and assessed the content of erythroid nucleated cells in the spleen and bone marrow under the existing microenvironment. For a pure population of CD71+ erythroid cells, we assessed the production of cytokines and the expression of genes that regulate the immune response. Our findings show changes in the cellular composition of the bone marrow and spleen during hypoxia, as well as changes in the composition of the erythroid cell subpopulations during acute hypoxic exposure in the form of a decrease in orthochromatophilic erythroid cells that are ready for rapid enucleation and the accumulation of their precursors. Cytokine production normally differs only between organs; this effect persists during hypoxia. In the bone marrow, during hypoxia, genes of the C-lectin pathway are activated. Thus, hypoxia triggers the activation of various adaptive and compensatory mechanisms in order to limit inflammatory processes and modify metabolism.